2020
DOI: 10.1093/infdis/jiaa753
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2–Induced Immune Activation and Death of Monocyte-Derived Human Macrophages and Dendritic Cells

Abstract: Studies of SARS-CoV-2-infected patients and experimentally infected animals indicate a critical role for augmented expression of pro-inflammatory chemokines and cytokines in severe disease. Here, we demonstrate that SARS-CoV-2 infection of human monocyte-derived macrophages (MDMs) and dendritic cells (MDDCs) was abortive, but induced the production of multiple antiviral and pro-inflammatory cytokines (IFN-α, IFN-β, TNF, IL-1β, IL-6 and IL-10) and a chemokine (CXCL10). Despite the lack of efficient replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
132
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 42 publications
(55 reference statements)
30
132
9
1
Order By: Relevance
“…However, production of these cytokines was generally lower in comparison to SARS-CoV-2 monocyte-derived macrophage. Unlike earlier observations, this study observed minimal up-regulation of IP-10 [34]. Thus, in contrast to SARS-CoV-1, in vitro infections of DC show conflicting support for the idea that DCs act as a significant source of proinflammatory cytokines and point toward other cell types that may be contributors of the cytokine storms observed in severe COVID-19.…”
Section: And Innate Immunity To Covid-19contrasting
confidence: 99%
See 1 more Smart Citation
“…However, production of these cytokines was generally lower in comparison to SARS-CoV-2 monocyte-derived macrophage. Unlike earlier observations, this study observed minimal up-regulation of IP-10 [34]. Thus, in contrast to SARS-CoV-1, in vitro infections of DC show conflicting support for the idea that DCs act as a significant source of proinflammatory cytokines and point toward other cell types that may be contributors of the cytokine storms observed in severe COVID-19.…”
Section: And Innate Immunity To Covid-19contrasting
confidence: 99%
“…While cDC and pDC express little to no ACE2 [33], moDC have recently been shown to express ACE2, albeit less than Calu3 cells [27]. SARS-CoV-2 has been demonstrated to infect moDC, but the infection is abortive [27,34]. In addition to ACE2, SARS-CoV-2 may infect various DC subsets through interaction with CD147, another receptor which binds SARS-CoV-2.…”
Section: And Innate Immunity To Covid-19mentioning
confidence: 99%
“…While writing the present manuscript contradictory data were published claiming that SARS-CoV-2 induces an immune activation of hMDM (Zheng et al, 2020). These conflicting results might be the consequence of different methodologies used.…”
Section: Discussionmentioning
confidence: 77%
“…These conflicting results might be the consequence of different methodologies used. While we employed purified monocytes to generate macrophages in six days, Zheng and collaborators kept PBMC with M-CSF for four days and then for another 10 days when the cells became adherent (Zheng et al, 2020). Another important methodological difference is that our study used ELISA to detect cytokines while Zheng and collaborators analyzed mRNA by RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the systematic down-regulation of genes encoding MHC class II molecules is more likely explained by a direct interaction of cDCs with the virus. This prediction was also supported by evidence that the virus can infect monocyte derived DCs ( 28 ).…”
Section: Main Textmentioning
confidence: 62%